Video Conferencing Solution for Synchronous Follow-Up of Cloud-Based IT Practical Work - Yade, Lamine; Gueye, Amadou Dahirou; Gueye, Bounama; Lishou, Claude (International Journal of Online and Biomedical Engineering (iJOE), 2020)
In a difficult economic context in the world in general and in the countries of sub-Saharan Africa in particular where we seek to make maximum return on investments; this paper draws on part of cloud computing technologies to offer traditional universities the possibility of carrying out practical work via the cloud without using either physical IT equipment or physical practical rooms; and on the other hand, on videoconferencing technologies to ensure synchronous monitoring of this practical work. Thus, a cloud-based laboratory model for STEM disciplines is proposed in [1]. In the implementation of the model, we proposed the solution based on practical work in the field of IT. This paper document is an extension of [1] and offers a videoconferencing solution for monitoring practical work applied on the cloud for collaborative work between the teacher and the learners. In this new model, practical work is done using virtual machines from the cloud, but real-time monitoring is provided by a videoconferencing system, the following functionalities of which have been added: screen sharing, file sharing and virtual classroom recording.